Profile coffee cultivars sensory processed in dry and humid via after storage - Ribeiro, Bruno Batista; Nunes, Cleiton Antônio; Jesus Souza, Antonio Jackson; Montanari, Fernanda Faria; Silva, Virgílio Anastácio da; Viana Madeira, Raul Antônio; Piza, Clovis de (Coffee Science - ISSN 1984-3909, 2017)
The different types of post-harvest processing employed in coffee fruits may yield different beverages, whose sensory profile depends on environmental factors and management in the production process. All the processes involved in coffee production, from soil and climatic characteristics of the growing area to the adopted storage system, interfere in the coffee beverage quality. The objective of this research was to describe the sensory profile of different coffee varieties processed by dry (natural) and wet (demucilated), after one year of storage. Were evaluated sensorially four coffee cultivars (Red Catuaí IAC 144, Iapar 59, Yellow Bourbon e Paraíso MG H 419-1), of Coffea arabica L. of the 2012/2013 season with the completion of two post-harvest processing (natural and demucilated cherry) after one year of storage. Sensory analysis was performed by two accredited tasters and enabled through the protocol of the Specialty Coffee Association of America - SCAA. Cultivars behave differently in quality according to the adopted process. Coffees of the natural processing stood out in most sensory attributes evaluated in relation to demucilated coffees after one year of storage. The Red Catuaí IAC 144 and Iapar 59 showed better quality when subjected to natural processing. Already in demucilated coffees, highest scores were awarded the Yellow Bourbon cultivars and Paraíso.